EQA in Air Microbiology - PNAEQ 2019 - Cano, Manuela (2021)
EQA implemented in 2010; Evaluation of the air sampling and analysis for the quantification of airborne bacteria and fungi: Sampling equipment used; Culture media (2012); Incubation temperature; Evaluation at 2 different sampling points (different 2 rounds per year (summer and winter).